Anode-less all-solid-state batteries: recent advances and future outlook. (1st March 2023) - Lee, Nohjoon; Oh, Jihoon; Choi, Jang Wook
Abstract: While all-solid-state batteries have built global consensus with regard to their impact in safety and energy density, their anode-less versions have attracted appreciable attention because of the possibility of further lowering the cell volume and cost. This perspective article summarizes recent research trends in anode-less all-solid-state batteries (ALASSBs) based on different types of solid electrolytes and anticipates future directions these batteries may take. We particularly aim to motivate researchers in the field to challenge remaining issues in ALASSBs by employing advanced materials and cell designs.